Effect of Mycobacterium bovis infection in cattle on changes in appetite-related hormones - Aşkar, Şinasi; Aşkar, Tünay Kontaş; Güzel, Murat (Austral Journal of Veterinary Sciences, 2018)
There are limited studies available for appetite-related hormonal changes in bovine tuberculosis, therefore the purpose of this study was to determine the changes in appetite-related hormones (leptin, ghrelin, and nesfatin -1) of cattle with tuberculosis and to clarify their possible roles. A total of 30 cattle, comprising 15 clinically healthy cattle and 15 cattle infected with tuberculosis were enrolled in the study. The diagnosis of tuberculosis was performed by tuberculin skin test, and changes in the concentrations of ghrelin, leptin, nesfatin-1, lipid profile and muscular enzymes in cattle with tuberculosis were determined. It was found that nesfatin-1, ghrelin and muscular enzymes concentrations were higher in bovine infected with tuberculosis than in the healthy controls. On the other hand, leptin, triglyceride, low density lipoprotein (LDL), high density lipoprotein (HDL), and total cholesterol levels were all lower in the tuberculosis group when compared to the control group. In this study, we detected serum nesfatin-1 concentrations for the first time in Mycobacterium bovis infection in addition to the other known appetite-related hormones. The data suggest that increased concentrations of nesfatin-1 may play a role in weight loss in bovine tuberculosis, but there is a need for further studies to determine its exact role in the etiopathogenesis of bovine tuberculosis.